2018
DOI: 10.1016/j.ijrobp.2018.05.074
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Carbon-Ion Radiation Therapy for Locally Advanced Sinonasal Malignant Tumors: Subgroup Analysis of a Multicenter Study by the Japan Carbon-Ion Radiation Oncology Study Group (J-CROS)

Abstract: The results of our multicenter study have demonstrated that C-ion RT can provide excellent clinical outcomes with acceptable late toxicities in patients who have locally advanced sinonasal malignant tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 32 publications
3
59
0
Order By: Relevance
“…8 One of the possible explanation of achieving less local control in the current study as compared to previous C-ion RT report of sinonasal cancers 8 can be suboptimal coverage of target volume because of close proximity of target volume to critical OARs. Apart from the nasal cavity, majority of the patients had maxillary sinus and ethmoid sinus involvement (40%).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…8 One of the possible explanation of achieving less local control in the current study as compared to previous C-ion RT report of sinonasal cancers 8 can be suboptimal coverage of target volume because of close proximity of target volume to critical OARs. Apart from the nasal cavity, majority of the patients had maxillary sinus and ethmoid sinus involvement (40%).…”
Section: Discussionmentioning
confidence: 53%
“…The 2 and 5 years local control rates were 84.1% and 71.2%, respectively. 8 One of the possible explanation of achieving less local control in the current study as compared to previous C-ion RT report of sinonasal cancers 8 can be suboptimal coverage of target volume because of close proximity of target volume to critical OARs. It could be substantiated by the fact that patients who received GTV Dmin0.1cc ≥ 52Gy (RBE) (n = 11) had shown a trend toward improved local control as compared to patients with GTV Dmin0.1cc < 52 Gy (RBE) (n = 11), although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Our multicenter study (J-CROS 1402 HN) showed that CIRT was effective and safe for head and neck malignancies, particularly including radioresistant tumors. [9][10][11][12][23][24][25] Since April 2018, the public health insurance system in Japan has covered CIRT for head and neck malignancies, with the exception of radiosensitive oral, laryngeal, and pharyngeal squamous cell carcinoma.…”
Section: T a B L E 3 Univariate Analysis For Localmentioning
confidence: 99%
“…Theoretically, C‐ion RT has a potential advantage for non‐squamous cell malignant tumors of the nasopharynx in reducing toxicity by sparing critical organs adjacent to the nasopharynx and its higher probability of control of photon‐resistant tumors. Recently, there has been increasing evidence of its efficacy and safety for head and neck malignant tumors . However, to date, there are no reports of C‐ion RT for non‐squamous cell malignant tumors of the nasopharynx.…”
Section: Introductionmentioning
confidence: 99%